Improving Students’ Vocabulary Using Riddles Game A Classroom Action Research - Anggun Kurnia Ningrum; Dwi Riyanti; Regina Regina (Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura, 2019)
This research was aimed to find out how can riddles game improve students’ vocabulary. This research was conducted through classroom action research (CAR) design. This research used observation and measurement as the technique of data collection. The tools of data collection were observation checklist, field note, and vocabulary test. Then, the analysis strategy used in this research was qualitative analysis to analyze qualitative data and quantitative analysis to analyze quantitative data. The result of this research displayed that the students’ vocabulary mastery improved. Students were more enthusiastic in the learning process. They were more active in following the vocabulary learning process. Then, the mean score and individual score of students also improved. Based on the research findings, it can be concluded that riddles game can improve students’ vocabulary. The teacher can apply riddles game in teaching vocabulary.